Epidemiology of acute abdominal pain: a cross-sectional study in a tertiary care hospital of Eastern India - Thakur, Jiwesh Kumar; Kumar, Rakesh (International Surgery Journal, 2019)
Background: Acute abdomen is defined as “a spectrum of surgical, medical and gynecological conditions ranging from trivial to life threatening conditions, which require hospital admission, investigations and treatment. The possible causes of acute abdomen may range from benign and psychogenic pain to life threatening aortic dissection. This study aims to find out the etiological spectrum of surgical acute pain abdomen among patients attending emergency department of a medical college of Eastern India. Methods: An institution based, cross-sectional study was conducted from January- June 2018, among patients admitted with pain abdomen in IQ City Medical College and Narayna Hospital, Durgapur, West Bengal, India. Data were collected on the day of discharge, with the help of pre-tested, semi structured Schedule. Results: Total 8688 patients were admitted through emergency during data collection period. 1236 (14.2%) of them were admitted with complains of pain abdomen. Frequency of surgical and non-surgical pain abdomen was 6.0% and 8.2% respectively. Most consistent symptom and sign were pain abdomen and abdominal tenderness respectively. Most common cause of acute abdomen was acute appendicitis. It was present in 38.9% of cases followed by gall bladder pathology, renal/ ureteric colic, perforation peritonitis, intestinal obstruction, bowel ischemia in 21.0%, 14.2%, 13.7%, 7.8%, and 4.4% of cases respectively. Conclusions: About 15.0% of all emergency hospitalization is due to acute abdominal pain and about 40.0% of all acute abdominal pain was due to surgical causes. Most common cause of surgical acute abdomen was acute appendicitis.